RADIONUCLIDE INDICATION OF SENTINEL LYMPH NODES IN LARYNX AND LARYNGOPHARYNX CANCER - I. G. Sinilkin; V. I. Chernov; Ye. L. Choinzonov; S. Yu. Chizhevskaya; A. A. Titskaya; R. V. Zelchan (Бюллетень сибирской медицины, 2014)
Aim: to determine the possibility of radionuclide methods in the identification of "sentinel" lymph node (SLN) in larynx and laryngopharynx cancer patients.Material and methods: 17 patients with larynx and laryngopharynx cancer were included in research. In all patients for SLN visualization nanocolloid radiopharmaceutical was injection around tumor into mucous coat with the subsequent SPECT and radioguided study.Results: Sensitivity and specificity of SPECT and radioguided study for SLN identification were 100%. We found 22 SLN in 17 patients (from 1 to 2 per patient, on average 1.3). Most often SLN were located in the III level of a neck (lymph nodes around of carotid arteries) – 12 SLN (54.5%) and IIA level (under lower jaw lymph nodes) – 6 (27.2%). One SLN (4.5%) was localized in IV level and 3 nodes (13.6%) in VI level. In 2 patients (11.8%) metastasis in SLN were found. In these patients within 2 years cancer progressing was revealed. Fifteen patients (88.2%) had no metastatic in SLN and had no progressing of a cancer.Conclusions: Sensitivity and specificity of SPECT and radioguided study for SLN identification are 100%. In patients with metastatic SLN radical surgery with lymph node dissection is helpful.